Application of cold atmospheric plasma for decontamination of toxigenic fungi and mycotoxins: a systematic review - Oliveira, Amanda Cristina Dias de; Ali, Sher; Corassin, Carlos Humberto; Ullah, Sana; Pereira, Karina Nascimento; Walsh, James Leon; Hojnik, Nataša; Oliveira, Carlos Augusto Fernandes de (Frontiers in Microbiology, 2025)
IntroductionMicrobial contamination remains a vital challenge across the food production chain, particularly due to mycotoxins—secondary metabolites produced by several genera of fungi such as Aspergillus, Fusarium, Alternaria, and Penicillium. These toxins, including aflatoxins, fumonisins, ochratoxins, and trichothecenes (nivalenol, deoxynivalenol, T2, HT-2). These contaminants pose severe risks to human and animal health, with their potential to produce a variety of different toxic effects. Notably, up to 50% of global cereal production is affected by mycotoxin contamination, leading to significant economic losses. Current research focuses on innovative technologies to mitigate mycotoxins, with cold atmospheric pressure plasma emerging as a promising decontamination method.MethodThis systematic review aimed at describing recent advances in the application of cold atmospheric plasma for the decontamination of toxigenic fungi and mycotoxins.Results and discussionCold atmospheric plasma offers a sustainable and cost effective solution to preserve food quality while inactivating toxigenic fungi and degrading mycotoxins. Through the generation of reactive oxygen and nitrogen species, cold plasma disrupts fungal cell integrity, hinders spore germination, and inhibits toxin biosynthesis. Additionally, cold atmospheric plasma-driven degradation of mycotoxins involves structural modifications, breaking key molecular bonds that reduce toxicity. The effectiveness of cold plasma depends on operational parameters and the specific characteristics of the treated food, with notable efficacy in degrading aflatoxin B1 and deoxynivalenol by converting them into less toxic substances and inhibiting their spores and DNA responsible for their biosynthesis. While the data demonstrates that cold atmospheric plasma has minimal impact on food composition, further research is needed to fully assess the nature of the degradation products of mycotoxins, its influence on food quality attributes and to optimize application strategies for different products.